Use of 3-D Models for Surgical Planning of a Malunion in a Dog. (25th March 2022) - Muroi, Norihiro; Fujii, Kiyohisa; Shimada, Masakazu; Kanno, Nobuo; Harada, Yasuji; Hara, Yasushi
Abstract : Background . An 8-year-old, 18.9 kg, male, intact Kai Ken with a femoral shaft fracture experienced recurrent implant breakage after two fracture reductions using an internal fixator. Objectives . This case report is aimed at using a three-dimensional (3-D) printer to diagnose residual femoral rotational deviation. Implant failures and malunion occurred after two attempts at synthesis. Thus, a 3-D model was designed for preoperative planning of a third surgery. Methods . To evaluate the alignment in the postoperative state after the second surgery, we removed a broken plate from the affected limb. Subsequently, a computed tomography image produced a bone replica using 3-D printing. The distal fragment was fixed and rotated externally by 42°. In addition to correcting the rotational deformity of the femur, we used an intramedullary pin and two locking plates to stabilize the proximal and distal femoral fracture segments. Results . The bone union was confirmed four months after surgery, and no postoperative complications were observed 11 months after surgery. Conclusion . 3-D printing is a valuable tool that increases the accuracy of presurgical planning.